2005
DOI: 10.7863/jum.2005.24.11.1491
|View full text |Cite
|
Sign up to set email alerts
|

Absence of a Relationship Between Umbilical Cord Thickness and Coiling Patterns

Abstract: Objective. The purpose of this study was to evaluate a relationship between the umbilical cord thickness and cord coiling patterns during the fetal sonographic anatomic survey in the second trimester of pregnancy. Methods. This was a prospective study of 470 patients with singleton pregnancies who had a fetal anatomic survey with recorded umbilical coiling patterns between 18 and 23 weeks' gestation. The umbilical cord thickness was assessed as an umbilical diameter at the level of the fetal abdominal cord ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 14 publications
(19 reference statements)
1
6
0
Order By: Relevance
“…This is in agreement with the studies reported by Predanic et al that the UCI is not associated with the thickness of umbilical cord or fetal weight 16. Also this is in agreement with the study reported by Degani et al that the UCI was not associated with the umbilical arterial Doppler index 5.…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with the studies reported by Predanic et al that the UCI is not associated with the thickness of umbilical cord or fetal weight 16. Also this is in agreement with the study reported by Degani et al that the UCI was not associated with the umbilical arterial Doppler index 5.…”
Section: Discussionsupporting
confidence: 93%
“…Predanic and Perni [22] evaluated the relationship between the umbilical cord thickness and cord coiling patterns during the fetal sonographic anatomic survey in the 2nd trimester of pregnancy. They reported that the UCI or umbilical coiling pattern did not correlate with umbilical cord thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Some have shown an association between UCI and SGA, but did not find any correlation between UCI and a low 5-min Apgar score, not even with SGA by some. 2,12 Most of the pregnancies with polyhydramnios in the present report had had umbilical cord with hypercoiling (3 of 5; 60%; p=0.002). The basis for this association could be that twisting of the umbilical cord is a result of the rotary movement imparted to the embryo, probably increased liquor amnii promotes more rotary movement of the foetus resulting in more coiling.…”
Section: Discussionmentioning
confidence: 83%
“…There is some evidence that adverse antenatal and perinatal events could be predicted and/or evaluated by cord thickness and amount of Wharton's jelly, lack of or excess cord coiling, and umbilical vein blood flow patterns. 2 The umbilical cord is prone to compression or torsion with ensuing interruption of blood flow. It has been accepted that coiling provides protection against these stressors, therefore providing uninterrupted blood supply to the fetus.…”
Section: Introductionmentioning
confidence: 99%